Fetal and maternal outcome of severe pre-eclampsia remote from term: expectant versus interventional management - Trivedi, Zeel; Gokhale, Ashish; Agarwal, Shonali; Bhatt, Vandana; Memakiya, Krishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This study was conducted to compare the safety and effect on maternal and perinatal outcome of expectant versus interventional management in women with preterm severe preeclampsia with gestational age between 28 to 34 weeks. Methods: This was a non-blinded prospective analytical study carried out in the department of obstetrics and gynaecology, SSG hospital, Vadodara from January 2021-December 2021. 40 women diagnosed with severe pre-eclampsia remote from term meeting the inclusion criteria were divided in two groups (20 in each). First group comprised of women undergoing interventional management i.e. prompt delivery and the second group comprised of women undergoing expectant management till 34 completed weeks. The women in the expectant management underwent pregnancy termination before 34 weeks if any complication arises (e.g. anhydramnios, abruption, eclampsia etc). Results: The mean prolongation of pregnancy in the expectant management group was 11.45 days (range: 4-35 days). There was no increase in incidence of maternal complications (p value: 0.003). The fetal outcome was favourable in the expectant management group in terms of higher gestational age at delivery (33 versus 31 weeks; p value: 0.001), higher birth weight (1.7 versus 1.5 kg; p value: 0.05), higher APGAR score at 1 minute (7.5 versus 7; p value :0.05), lesser incidence of neonatal complications (55% versus 95%; p value 0.003). Conclusions: Considering the results of this study, it can be concluded that expectant management is recommended in patients with severe preeclampsia remote from term with intensive monitoring.